Case of ovarian hyperstimulation and oocyte pick‐up during very early period of unnoticed pregnancy followed by ongoing normal pregnancy. Issue 4 (12th February 2016) - Takenaka, Hiroshi; Nakao, Kazuki; Horikawa, Michiharu; Negishi, Hiroaki
Abstract : We report a case of unnoticed pregnancy that was maintained during low estrogen and progesterone circumstances, that showed menses‐like bleeding, and was then discovered after ovarian hyperstimulation during the next period. The patient was 39 years old and primigravid. She underwent intrauterine insemination, followed by luteal support with human chorionic gonadotrophin and progestin; however, she experienced menstruation‐like bleeding 15 days later. As low estradiol and progesterone levels were confirmed on the 2nd day of bleeding, ovarian hyperstimulation of short protocol for in vitro fertilization was commenced. Although 13 mature follicles were observed, only six oocytes were retrieved and one developed into a blastocyst. Four days after oocyte pick‐up, a gestational sac was seen in utero . The fetus is currently growing uneventfully. This case suggests that pregnancy can be maintained during ovarian hyperstimulation, even if menstruation‐like bleeding is shown in low‐progesterone circumstances.